PROCESS OF IODINE REDUCTION BY FORMIC ACID TO REGENERATE HI IN POLIOL CONVERSION TO HYDROCARBON - Nazwa Nur Fatihah, Amanda
Along with the economic and technological developments, the need for energy especially for transportation fuels has increased. However, the dwindling availability of fossil fuels and the world economy which is starting to move towards renewable energy has led to innovations related to the conversion of biomass to hydrocarbon fuels. In 1995, Robinson et al. Conducted an experiment on the conversion of Poliols to hydrocarbons. Poliol is a chemical derivative of sugar that has a hydroxyl group and is one of the biomass derivatives. In his experiment, Robinson (1995) reduced Poliol in the form of sorbitol with HI at a temperature of 110-127oC and used H3PO3 as a reducing agent from I2 to HI to minimize the use of HI which was very expensive. However, H3PO3 has a high price, so modifications are needed to overcome these shortcomings. One of the reducing agent candidates for the reduction of iodine to HI is formic acid which can be produced from biomass and has a cheaper price. However, the reduction of I2 by formic acid was much slower than using H3PO3. This research focuses on increasing the speed of the I2 reduction process by formic acid with the help of H3PO4 catalysts, Triethylamine (TEA), and Dimethyl sulfoxide solvent on the conversion of sorbitol to hydrocarbons carried out at temperatures of 100-120oC with a reaction time of 2-6 hours. The analysis carried out is an analysis of the content of sorbitol and residual iodine and the levels of CO2 formed. In the experiment using H2PO4-, the I2 reduction reaction speed was still slower which caused I2 solids to be formed during the reaction. In the experiment using Triethylamine, sorbitol conversion was obtained by 27.78% (6 hours reaction). This result is still too small because triethylamine which should be increased reduction power of formic acid is reacted with iodine. In the experiment using DMSO-water solvent, sorbitol conversion was obtained by 32.74% (3 hours reaction). The conversion is still too low because the amount of I-/OH used is too small.